Bahasa Inggris - Nur Hidayanti; Winarni Winarni; Mirasanti Wahyuni (Faculty of Economic and Business Universitas STIKUBANK, 2023)
The purpose of this research is to identify and analyze the effect of OER, NIM, NPL, CAR, and LDR toward ROA at PT Regional Development Banks in Indonesia for the period 2016-2021. The population in this research is PT Regional Development Bank in Indonesia. The sampling technique used is purposive sampling technique and gained 25 Banks. Secondary data is sourced from Financial Reports published by every Regional Development Bank in Indonesia during the 2016-2021 period and the official website of the Financial Services Authority. Method of data analysis in this research is multiple linear regression analysis. The analysis technique uses the F test, t test, and the determination coefficient test (R2). The results of this research indicate that OER, NIM, NPL, CAR, and LDR simultaneously have a significant effect on ROA. Based on the results of the t test, it can be concluded that OER and NPL have a significant effect and have a negative coefficient direction on ROA, NIM and LDR have a significant effect and have a positive coefficient direction on ROA. Meanwhile, CAR has no significant effect and has a negative coefficient on ROA. The results of multiple linear regression analysis obtained the Adjusted R2 value of 0.945, this indicates that the independent variable contributes 94.5% influence on the dependent variable while the remaining 5.5% is influenced by other variables not examined in this research.